Socio-economic status and early outcome from coronary artery bypass grafting. Issue 10 (19th March 2009) - Gibson, P H; Croal, B L; Cuthbertson, B H; Gibson, G; Jeffrey, R R; Buchan, K G; El-Shafei, H; Hillis, G S
Abstract : Objective: To determine the effects of socio-economic status (SES) on the outcome of coronary artery bypass grafting (CABG). Design: Prospective cohort study. Setting: Regional cardiac surgical unit. Patients: 1994 consecutive patients undergoing non-emergency CABG. Measures: SES was determined from the patient's postcode using Carstairs tables. The primary end-point was all-cause mortality at 30 days. Results: There were 50 deaths (2.5%) within 30 days of surgery. A higher Carstairs score demonstrated a trend towards increased 30-day mortality (odds ratio (OR) 1.09 per unit, 95% CI 1.00 to 1.20, p = 0.06). In a backward conditional model, including other predictors of early mortality, Carstairs scores were independently predictive (OR 1.12 per unit, 95% CI 1.01 to 1.24, p = 0.02). In a model including only Carstairs scores and the EuroSCORE, both were independent predictors of this outcome (OR for Carstairs score 1.11 per unit, 95% CI 1.00 to 1.22, p = 0.04). The 30-day mortality increases in each quartile of Carstairs scores, with patients in quartile 4 (most deprived) at significantly higher risk compared with quartile 1 (uncorrected OR 2.53 per unit, 95% CI 1.04 to 6.15; OR corrected for EuroSCORE, 2.56 per unit, 95% CI 1.03 to 6.34, p = 0.04 for both). Similarly, patients in the least affluent quartile were twice as likely to suffer a serious complication as those in the most affluent quartile (OR 2.14 per unit, 95% CI 1.32 to 3.46, p = 0.002). This increased risk was also independent of the EuroSCORE. Conclusions: Lower SES is associated with a poorer early outcome following CABG and is independent of other recognised risk factors.